2020
DOI: 10.3390/molecules25204604
|View full text |Cite
|
Sign up to set email alerts
|

Protease Inhibitory Effect of Natural Polyphenolic Compounds on SARS-CoV-2: An In Silico Study

Abstract: The current pandemic, caused by SARS-CoV-2 virus, is a severe challenge for human health and the world economy. There is an urgent need for development of drugs that can manage this pandemic, as it has already infected 19 million people and led to the death of around 711,277 people worldwide. At this time, in-silico studies are providing lots of preliminary data about potential drugs, which can be a great help in further in-vitro and in-vivo studies. Here, we have selected three polyphenolic compounds, mangife… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 42 publications
0
21
0
Order By: Relevance
“…The emergence of the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has caused a global health crisis with over 2 million deaths worldwide, compelling rapid drug development for potential therapeutics. Several major protein targets have been identified for inhibition of SARS-CoV-2 function and surveyed through molecular simulation for predicted binding affinity with repurposed and novel drugs, these include the RNA dependent RNA polymerase ( Procacci et al, 2020 ; Wakchaure et al, 2020 ) (RdRp) that replicates the RNA genome, the main protease ( Macchiagodena et al, 2020b ; Ngo et al, 2020b ; Chowdhury et al, 2020 ; Gupta et al, 2020 ; Gupta and Zhou, 2020 ; Jukic et al, 2020 ; Li et al, 2020 ; Milenković et al, 2020 ; Tejera et al, 2020 ; Aghaee et al, 2021 ; Bhardwaj et al, 2021 ) (3CL M pro ) that mediates replication and transcription, the spike protein ( Patil et al, 2021 ) involved in initiating infection by penetrating the host cell, S-adenosyl-methionine dependent methyltransferase ( Sk et al, 2020 ) (nsp16) that adds the 5′-cap to mRNA essential for stability, envelope protein ( Dey et al, 2020 ) that is involved in virion assembly and budding, Papain-like protease that functions in viral replication and immune response evasion ( Bosken et al, 2020 ), and the host serine protease TMPRSS2 ( Singh et al, 2020 ) that primes the spike protein. Alanine scanning is combined with MM-PBSA to identify the hot-spot binding residues GLU166 and GLN189 on M pro as critical sites for inhibitors to target ( Aghaee et al, 2021 ).…”
Section: Applications To Drug Discoverymentioning
confidence: 99%
“…The emergence of the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has caused a global health crisis with over 2 million deaths worldwide, compelling rapid drug development for potential therapeutics. Several major protein targets have been identified for inhibition of SARS-CoV-2 function and surveyed through molecular simulation for predicted binding affinity with repurposed and novel drugs, these include the RNA dependent RNA polymerase ( Procacci et al, 2020 ; Wakchaure et al, 2020 ) (RdRp) that replicates the RNA genome, the main protease ( Macchiagodena et al, 2020b ; Ngo et al, 2020b ; Chowdhury et al, 2020 ; Gupta et al, 2020 ; Gupta and Zhou, 2020 ; Jukic et al, 2020 ; Li et al, 2020 ; Milenković et al, 2020 ; Tejera et al, 2020 ; Aghaee et al, 2021 ; Bhardwaj et al, 2021 ) (3CL M pro ) that mediates replication and transcription, the spike protein ( Patil et al, 2021 ) involved in initiating infection by penetrating the host cell, S-adenosyl-methionine dependent methyltransferase ( Sk et al, 2020 ) (nsp16) that adds the 5′-cap to mRNA essential for stability, envelope protein ( Dey et al, 2020 ) that is involved in virion assembly and budding, Papain-like protease that functions in viral replication and immune response evasion ( Bosken et al, 2020 ), and the host serine protease TMPRSS2 ( Singh et al, 2020 ) that primes the spike protein. Alanine scanning is combined with MM-PBSA to identify the hot-spot binding residues GLU166 and GLN189 on M pro as critical sites for inhibitors to target ( Aghaee et al, 2021 ).…”
Section: Applications To Drug Discoverymentioning
confidence: 99%
“…It has been demonstrated that the serine protease TMPRSS2 is needed for S protein priming and host cell entry [ 11 ]. Virtual screening of natural SM libraries against a TMPRSS2 structure built by homology modeling detected several potential protease inhibitors, including norsesquiterpenes, diterpenes and xanthones, [ 133 , 164 , 172 ] alkaloids, [ 173 ] chalcones, [ 164 ] coumarins, [ 173 ] and flavonoids. [ 174 ] Interestingly, SARS-CoV infectivity is reportedly associated TMPRSS2 expression levels, which are induced by androgens and suppressed by estrogens, implying that natural estrogen receptor agonists (e.g., genistein) and androgen receptor antagonists (e.g., atraric acid, indole-3-carbinol, niphatenone B) could impact SARS-CoV-2 infection [ 175 , 176 , 177 , 178 ].…”
Section: Nps With Anti-hcov Potentialmentioning
confidence: 99%
“…They found 28 bioactive compounds, including CHEMBL3236740, CHEMBL1447944 and others, were identified as effective anti-SARS-CoV-2 drug candidates ( Figure 3 ). Singh et al [ 89 ] identified several compounds, glucogallin, mangiferin, N3, remdesivir and X77 which had stronger binding affinities with M pro . Furthermore, the results suggest that the phlorizin had the lowest binding free energy toward M pro ( Figure 4 ), followed by glucogallin and mangiferin.…”
Section: Cadd Against Sars-cov-2: Targeting M Promentioning
confidence: 99%